1997
DOI: 10.1002/(sici)1097-4636(199724)38:4<370::aid-jbm10>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Failure mechanisms of anterior cruciate ligament prostheses:In vitro wear study

Abstract: Previous retrieval studies analyzing the cause of failure of anterior cruciate ligament (ACL) prostheses identified a wear mechanism. However, the relative importance of yarn on bone compared to yarn on yarn wear has not been clearly understood. Therefore, the objective of this study was to elucidate which type of wear is the dominant cause of clinical failure. A variety of ACL prosthetic structures were exposed to two in vitro tests: one for yarn on yarn and the other for a novel yarn on bone wear test system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…They identified 3 mechanisms of prosthetic ACL failure: (1) inadequate fibre abrasion resistance against osseous surfaces, (2) flexural and rotational fatigue of the fibres, and (3) loss of integrity of the textile structure due to unpredictable tissue infiltration during healing. A further in vitro study of synthetic grafts by Poddevin et al found that the predominant cause of failure was yarn on bone abrasion [32]. It is interesting to note that in the current study, all failures occurred at the femoral tunnel aperture.…”
Section: Discussionmentioning
confidence: 48%
“…They identified 3 mechanisms of prosthetic ACL failure: (1) inadequate fibre abrasion resistance against osseous surfaces, (2) flexural and rotational fatigue of the fibres, and (3) loss of integrity of the textile structure due to unpredictable tissue infiltration during healing. A further in vitro study of synthetic grafts by Poddevin et al found that the predominant cause of failure was yarn on bone abrasion [32]. It is interesting to note that in the current study, all failures occurred at the femoral tunnel aperture.…”
Section: Discussionmentioning
confidence: 48%
“…These show suitable mechanical and functional results in the short term after surgery. Long-term clinical outcomes are limited due to mechanical disparity, lower abrasion resistance of synthetic ligaments, and limited integration between the graft and host tissue [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The major cause of failure for these prostheses is through cellular effects induced by wear debris, a result of polyethylene surface attrition at prosthetic surfaces . This same mechanism leads to problems with ligament and tendon prostheses …”
Section: Introductionmentioning
confidence: 99%